KEPEMIMPINAN KARISMATIK KH. MOH. HASIB WAHAB DI PONPES BAHRUL ULUM TAMBAKBERAS JOMBANG - Hasyim Ari Asyari (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Abstract This study aims to describe the charismatic leadership of kiai Moh. Hasib Wahab at the boarding school Bahrul Ulum Tambakberas, Jombang. The method in this study is qualitative with interview techniques, research observations, and document studies. Interviews were conducted with the board of the pondok, santri and the external community. Data analysis uses four paths, namely data reduction, data display, reduction and conclusion. This studies show that charismatic leadership KH. Hasib Wahab at the Bahrul Ulum Islamic boarding school Tambakberas, Jombang showed good development. This is evidenced by the construction of good character that has attracted the attention of the public, increasing the number of students who until now reached +5,500 and improving education through its policies. Keyword: Charismatic Leadership, Quality, Kiai, Pesantren, Santri.